2009
DOI: 10.1152/japplphysiol.00121.2009
|View full text |Cite
|
Sign up to set email alerts
|

A brief bout of exercise alters gene expression and distinct gene pathways in peripheral blood mononuclear cells of early- and late-pubertal females

Abstract: Radom-Aizik S, Zaldivar F Jr, Leu S, Cooper DM. A brief bout of exercise alters gene expression and distinct gene pathways in peripheral blood mononuclear cells of early-and late-pubertal females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
61
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 30 publications
(28 reference statements)
2
61
0
Order By: Relevance
“…Several genes in the “cytokine receptor functional group” have been shown to change with exercise. 19,20 Dramatic changes in leukocyte gene expression and alterations in extracellular cytokine concentrations that we observed in this study (namely increases in TGFβ1, P-selectin, IL-6, and TNF-α) suggest that leukocytes are reactive to the stress of exercise and that these alterations may contribute to exercise-induced allergy and asthma. 21,22 …”
Section: Discussionmentioning
confidence: 67%
“…Several genes in the “cytokine receptor functional group” have been shown to change with exercise. 19,20 Dramatic changes in leukocyte gene expression and alterations in extracellular cytokine concentrations that we observed in this study (namely increases in TGFβ1, P-selectin, IL-6, and TNF-α) suggest that leukocytes are reactive to the stress of exercise and that these alterations may contribute to exercise-induced allergy and asthma. 21,22 …”
Section: Discussionmentioning
confidence: 67%
“…Up-regulated genes were noted in several categories including immune, inXammatory (more pro-inXammatory than anti-inXammatory) and stress (heat shock proteins and hypoxia-inducible factor-1, HIF). A more recent paper (Radom-Aizik et al 2009) used 20 young female participants, and found altered expression of 622 genes in 11 diVerent gene pathways. SigniWcant gene pathway changes were related to inXammation, stress (heat shock protein-70) and apoptosis (fas ligand) pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have evaluated whether such an association exists among women with a BRCA1 mutation (10)(11)(12)(13). Cancer-protective mechanisms of physical activity have mainly focused on alterations in levels of sex hormones, inflammatory markers, and growth factors (14)(15)(16). It is plausible that such changes are due to physical activity-induced transcriptional changes, as physical activity has been shown to induce widespread transcriptional effects (17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%